2017
DOI: 10.18632/oncotarget.17879
|View full text |Cite
|
Sign up to set email alerts
|

trans-4,4’-Dihydroxystilbene (DHS) inhibits human neuroblastoma tumor growth and induces mitochondrial and lysosomal damages in neuroblastoma cell lines

Abstract: In view of the inadequacy of neuroblastoma treatment, five hydroxystilbenes and resveratrol (Resv) were screened for their cytotoxic property against human neuroblastoma cell lines. The mechanism of cytotoxic action of the most potent compound, trans-4,4’-dihydroxystilbene (DHS) was investigated in vitro using human neuroblastoma cell lines. DHS was also tested in a mouse xenograft model of human neuroblastoma tumor. The MTT, sub-G1, annexin V and clonogenic assays as well as microscopy established higher cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Previous published literature in vitro and in vivo studies suggested the anticancer effect of GLA. GLA reduced tumor growth in a WBC256 rat model; it also inhibited the cell growth of various rat carcinogenesis cell lines and human neuroblastoma cell lines 19,20. GLA treatment down-regulated mammary gland carcinogenesis and tumor growth.…”
Section: Introductionmentioning
confidence: 91%
“…Previous published literature in vitro and in vivo studies suggested the anticancer effect of GLA. GLA reduced tumor growth in a WBC256 rat model; it also inhibited the cell growth of various rat carcinogenesis cell lines and human neuroblastoma cell lines 19,20. GLA treatment down-regulated mammary gland carcinogenesis and tumor growth.…”
Section: Introductionmentioning
confidence: 91%
“…The pharmacological action of 4,4 -DHS in the human neuroblastoma IMR32 cells was mediated by the destabilization of mitochondrial and lysosomal membranes, associated with modulation of several related pro-and anti-apoptotic cascades of proteins. Additionally, in the animal model, the oral administration of 4,4 -DHS for one month was well tolerated and demonstrated a greater therapeutic potential than resveratrol [56]. More recently, Saha et al demonstrated that in melanoma cells, 4,4 -DHS acts by inducing apoptosis and cell cycle arrest in G1 phase and inhibiting cell proliferation.…”
Section: Dihydroxystilbenementioning
confidence: 99%
“…4,4′-DHS ( Figure 3 ) in the human neuroblastoma IMR32 cells was shows destabilization of mitochondrial and lysosomal membranes. Its cause lysosomal membrane permeabilization to reduce MMP/caspase-3 activation through the production of cathepsins B, L and D, and the cathepsins [ 88 ].…”
Section: Hydroxylated Resveratrol Derivativesmentioning
confidence: 99%